Intersectionality and addressing equity in agriculture, nutrition, and health - Malapit, Hazel J.; Quisumbing, Agnes R.; Hodur, Janet (International Food Policy Research Institute, 2020)
The UN Sustainable Development Goals were established to build a better and more sustainable future for all. Progress toward development objectives has been uneven over time, and the disadvantaged tend to suffer disproportionately, particularly in times of severe shocks or crises like the COVID-19 global pandemic. The inclusion of the phrase “for all” is a good reminder that meeting our global goals will require paying particular attention to equity and ensuring no one is left behind. To consider equity, one must acknowledge that not everyone starts from the same set of circumstances, and assess how unfair, unjust, and exclusionary social and political processes have created that situation. Addressing inequity involves being mindful of those processes and removing barriers that prevent people from participating fully in decisions that determine how goods, opportunities, or resources are distributed. It is subtly, yet importantly, different from equality, which involves ensuring those goods, opportunities, or resources are divided equally among a group. In order to work toward equality, one must ensure equity has been achieved.